CYBERSECURITY IN THE CIVIL AVIATION AND EXISTING CHALLENGES - Svanadze, Vladimer (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose of the article: by this article the author wants to reveal the provisions and features regulations, structures and standards of International Organizations works in Cybersecurity in The Civil Aviation. The methodological basis of the research comprises general scientific and special methods. Results: the legislation of ICAO and ITAO is vitally crucial to ensure cybersecurity for the civil aviation. All stakeholders, in particular, public and private sectors as wells as the representatives of academia should be involved in the process of protecting critical infrastructure of the Civil Aviation. Discussion: cyber security in civil aviation is mainly based on the cyber technologies used to increase the safety and efficiency of air transport. At the same time, the interconnection of systems and reliance on technology is a prerequisite for the emergence of new cyber threats and risks. An interconnected computer system is widely used in the aviation industry.